(untitled) (Kriminalističke teme, 2022)
Organized crime is a continuous activity whose illicit activities lead to profit. DNA analysis is important in solving both individual and organized crimes. One of the most important tools in finding and identifying perpetrators with the help of DNA analysis is the CODIS System or DNA registry. The existence of a database makes it easier to identify returnees of some crimes, then connect different people with one person at the scene, as well as connect multiple people with one person. The importance of DNA profiles and DNA databases in organized crime research is great. National legislation regarding the collection and storage of samples for DNA analysis differs. Thanks to DNA expertise and DNA as evidence, in a large number of court judgments we have appropriate penalties for committing crimes. From this research, 36% of the success of obtaining relevant DNA profiles for solving the crime of murder, and in the case of attempted murders was determined.